A Study on Characteristics of Semi-Natural Hatchery Habitat for Olive Ridley Sea Turtle Lepidochelys olivacea (Eschscholtz, 1829) Conservation: A Case Study of Batu Hiu Beach, Pangandaran, West Java, Indonesia - Faddilah, Thallita Nasywa; Hasan, Zahidah; Arief, Mochamad Candra Wirawan; Herawati, Titin (Journal Omni-Akuatika, 2024)
Sea turtle populations have declined due to habitat destruction and the widespread collection of eggs for commercial purposes. This study assessed the characteristics and suitability of semi-natural hatchery habitats for Olive Ridley Sea Turtles (Lepidochelys olivacea) at Batu Hiu Beach, Pangandaran, West Java, Indonesia, from June 1-July 31, 2023. The survey method and purposive sampling were employed to determine nesting sites based on turtle landing points.Biophysical habitat measurements were analyzed descriptively and statistically using one-way ANOVA and Tukey's post hoc test to compare sand temperature, sand humidity, and air humidity. An L. olivacea landed at site 4, laying 73 eggs in a natural nest with 34 cm nest depth and 24 cm nest diameter. Semi-natural nests measured 37 cm nest depth and 26 cm in nest diameter. The sand type at Batu Hiu Beach was characterized by black sand grains and fine sand substrate with a percentage of 51.02%. The temperature within the hatchery ranged from 25.3°C to 42.1°C.  with average of 29.7 ± 1.88 °C.The sand humidity in the hatchery ranged from 2% to 14%, with an average daily humidity of 10 ± 0.22 %. The air humidity within the hatchery ranged from 56% to 94%, with a daily average of 85 ± 0.05 %. Based on all the analyzed parameters, the hatchery at Batu Hiu Sea Turtle Preservation were suitable with the nest criteria by Technical Guidelines for Sea Turtle Conservation Management by DKP for the hatching of L. olivacea eggs, with a hatching success rate of 85%.Keywords: Lepidochelys olivacea, temperature, humidity, sand type, hatching success